Argumentação na revista Raça Brasil: um estudo da retórica antirracista - Mirian Lucia Brandao Mendes (2011)
This work is aimed at identifying the main discourse and argumentative strategies used in the construction of statements in the section Race Opinion of the Raça Brasil magazine. As an instrument for analysis and research, we have relied on the argumentation theory of Chaïm Perelman and Lucie Olbrechts-Tyteca on New Rhetoric. Initially, we take a brief step back to the period of African slavery in Brazil, by focusing on the formation of Quilombos (refuges for slaves and marginalized people at the time). Following that, we explain the concept of discourse proposed by Maingueneau and Charaudeau (2008) and define what we call rhetoric argumentation. In the analysis of the corpus itself, we start presenting the notion of ethos, which is regarded as relevant for our analyses. Then, we proceed to identify the starting points of the argumentation on the corpus, object of our analyses. Finally, we propose a thinking process through which we relate the concepts of auditorium and polyphony.